Strategi Kebijakan Mengatasi Pengangguran Terbuka Lulusan Sekolah Menengah Kejuruan (SMK) di Kabupaten Bintan - Jenawi, Billy; Sujarwani, Riau; amira, shaza (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Unemployed are people who do not have the opportunity to work, but are looking for work or residents who are not looking for work because they feel it is impossible to get a job. It can be seen that vocational education is still a problem to get jobs because residents with vocational education are not necessarily able to guarantee to get jobs easily and also lack of human resources in each individual. This research was conducted on the basis of finding out how the policy strategy to overcome open unemployment was for graduates of Vocational High Schools (SMK) in Bintan Regency. The purpose and intent of this paper is to find out how the policy strategy to overcome open unemployment is for graduates of Vocational High Schools (SMK) in Bintan Regency. In this study, the method used is descriptive qualitative, in which the author must obtain the widest and deepest possible information. So it can be concluded from the research that there is no policy strategy to overcome open unemployment for graduates of Vocational High Schools from the Bintan Regency Manpower Office and Riau Islands Province Education Office. However, to overcome this unemployment, the Manpower Office of Bintan Regency and the Riau Islands Province Education Office have programs to reduce the open unemployment rate of Vocational High School graduates in Bintan Regency.